Preparation and tribological behaviors of plasma sprayed NiAl-Cu/graphite nanosheets composite coating. (March 2022) - Yanhan, Feng; Jianhua, Fang; Ping, Liu; Kecheng, Gu; Shuang, Su; Jiang, Wu; Zeqi, Jiang
Abstract: Graphite nanosheets (GNs) is an outstanding nanofiller in composite coatings. However, it is difficult to use in plasma spray because it is too light to be mixed with spraying powders. This paper aims to report on a Cu/GNs composite powder synthesized by the ascorbic acid reduction method and its application on plasma spraying. Scanning electron microscopy revealed the anchoring of the copper particles on the GNs, and thus the composite powder could be uniformly mixed with NiAl spraying powder. Reciprocating tribological tests exhibited a 13.8% and 17.2% reduction for the friction coefficient and wear rate of the composite coating. A GNs contained transfer layer was discovered at the wear scar, which was considered as the anti-friction and anti-wear layer. Graphical abstract: ga1 Highlights: Graphite nanosheets load copper particles (Cu/GNs) composite powder is synthesized Cu/GNs powder is applied on plasma spray to manufacture GNs-metal composite coating Tribological properties of the composite coating is obviously improved